Revisión de estudios historiográficos sobre la salud pública brasileña - Duarte Nunes, Everardo (1996)
The main aim of this report is to outline a first approach on the studies dealing with public health history in Brazil. This presentation does not intend to embrace all the literature on this subject, either regarding diseases or institutions. Reports were limited to those emphasizing historical periods and presenting a general view of the public health development. After considering the instalation of Brazilian social medicine project -from colonial period to the first decades of nineteenth century- we analyzed studies comprising the public health history from 1870 to 1930. The period from 1889-1930, also known as Old Republic, with very specific characteristics in Braziliam socioeconomic and politic history, has been stressed. The principal emphasis is on the increasing importance that historical studies have been receiving, with a production where the austerity of historical research is associated to an analytical perspective directed to a complete understanding of the sociopolitical contexts that lead to sanitary practices.